Effects of Lactic Acid Bacteria and Organic Acids on Growth and Germination of Bacillus cereus - Wong, Hin-Chung (1988)
Growth and germination of vegetative cells and endospores of Bacillus cereus were affected by Streptococcus lactis, Streptococcus thermophilus, Lactobacillus acidophilus, and Lactobacillus bulgaricus in nonfat milk medium and by salts of organic acids in broth medium. Growth of the lactic acid bacteria was not affected by B. cereus. B. cereus increased rapidly to about 10(8) CFU/ml when cells were added at the beginning of growth of lactic acid bacteria; it was inactivated slowly when added after 24 h and rapidly when added after 72 h of lactic acid bacterial growth. Streptococci were more inhibitory to the growth of B. cereus than lactobacilli were at 24 h. Spore germination was not affected after 24 h, but it was inhibited after 48 and 72 h of lactic acid bacterial growth. Acetate was more inhibitory to the growth of vegetative cells, while formate was more inhibitory to spore germination. Acetate, formate, and lactate (all at 0.1 M) completely inactivated multiplication of B. cereus at pH 6.1, 6.0, and 5.6, respectively. Spores of B. cereus were more resistant to these organic acids compared with the resistance of vegetative cells. Formate, lactate, and acetate (all at 0.1 M) caused 50% inhibition of spore germination at pH 4.4, 4.3, and 4.2, respectively.